THE SINGLE MARKET AND THE “BICYCLE THEORY” OF THE EUROPEAN UNION POLITICS. DOES IT STILL WORK? - Ząbkowicz, Jerzy (Ekonomia i Prawo. Economics and Law, 2015)
Decades of liberalization have transformed the original structure of the EC common market, being a synonym of the validity of the Four Freedoms — free movement of persons, goods, services and capital — into an integral instrument for conducting EU economic policy, but not without many constraints, both formal and informal. The process of globalization of the world economy means, in the opinion of EU institutions, that currently the European Union more than ever needs a single market that would support reforms to boost growth and increase its competitiveness. The Single Market Acts of 2011 and 2012 suggest measures to further its development. It is treated as a continuous process. However, for many Member States the evolution of the single market is a kind of a perpetual transaction — a tender, in which a concession to EU group interests is expected equivalent of particular benefit. Quite often all concessions are treated by public authorities as downright harmful to the national interest, especially in times of economic and financial crisis. The aim of this paper is an attempt to answer the question why building consensus on further proceeding to the single market is seemingly more difficult to achieve than ever in the past? The problem looks even more serious, once we accept as a starting point the “bicycle theory”, which shows that the halting of the evolution of the single market may cause the opposite process — the disintegration of the EU market.